Governance capacity and strategic adaptation: Explaining the parliamentary decline of Indonesian Muslim-based parties in the 2024 election - Ari Ganjar Herdiansah; Muhammad Andi Firmansyah; Noor Sulastry Yurni Ahmad (Masyarakat, Kebudayaan dan Politik, 2026)
Although the overall electoral support for Muslim-based parties in Indonesia has been relatively stable since the Reformasi, the 2024 election represents a critical moment in which the PPP failed to pass the parliamentary threshold. This divergence raises the question: why did PPP break down while other major Muslim-based parties (PKS, PKB, PAN) persisted? Employing a qualitative comparative approach, this paper contends that electoral performance is shaped by the constitutive interplay of governance capacity and strategic adaptation. We show that PKS pursues bounded adaptation and relies on relatively high governance capacity to maintain loyalty among its core constituencies; PKB mixes established governance with high strategic adaptation in order to use NU based networks and presidential coattail effects; and PAN pairs relatively high governance capacity and aggressive demographic segmentation. By contrast, the demise of PPP is attributed to low or incoherent governance capacity, which renders its adaptive strategy sporadic and lacking credibility. Theoretically, this article shifts the analytical focus from static party institutionalization to dynamic organizational capability. It also argues that religious identity becomes an electoral asset when it is managed through a balance between internal governance and adaptation, with institutions strong enough to withstand the shocks of strategic pragmatism.